Manoel da Costa Athaíde : vida e obra documentada no ambiente artístico de MInas Gerais, 1762 a 1830 - Cenise Maria de Oliveira Monteiro (2024)
Manoel da Costa Athaíde, Mariana, MG, 1762-1830, a member of various religious lay associations, is the subject of this study. The research aims to understand the family, social and professional relationships of the painter, born into a family of fervent Catholics, made up of Portuguese and freed women. Mestre Athaíde lived through the artistic effervescence of Minas Gerais, working as a gilder, perspective painter and teacher of the art of painting. By analysing the manuscripts and collating the historiography of colonial art, the aim is to scrutinise and concatenate the information revealed, with the aim of constructing an up-to-date biography, encompassing the personal and military trajectory of the colonial painter, as well as his artistic training and his lapidary flourishing in the art of painting.